2003
DOI: 10.1046/j.1365-2672.2003.01826.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of bacterial community during bioremediation of an oil-polluted soil*

Abstract: Aim:To study the response of the bacterial community to bioremediation of a soil with an aged contamination of crude oil. Methods and Results: The bacterial community in laboratory soil columns during a 72-day biostimulation treatment was followed by analysing the number of total cultivable hydrocarbon-degrading bacteria, soil respiratory activity and the 16S-23S rDNA internal transcribed spacer homoduplex heteroduplex polymorphisms (ITS-HHP) of total soil bacterial DNA. ITS-HHP permits an estimate of both len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 37 publications
6
43
0
2
Order By: Relevance
“…Other authors have described both increases and reductions in diversity during biodegradation. Our results are similar to those reported by Andreoni et al (6) obtained with a PAH-contaminated soil, whereas Kaplan and Kitts (18) and Zucchi et al (41) reported increases in diversity during bioremediation of crude oil-contaminated soil.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Other authors have described both increases and reductions in diversity during biodegradation. Our results are similar to those reported by Andreoni et al (6) obtained with a PAH-contaminated soil, whereas Kaplan and Kitts (18) and Zucchi et al (41) reported increases in diversity during bioremediation of crude oil-contaminated soil.…”
Section: Resultssupporting
confidence: 92%
“…The few studies that have been described to date have been performed either with soils with low levels of PAH contamination (6,41,28) or with spiked soils (32), and there has not been accurate monitoring of the microbial population dynamics throughout the biodegradation process.…”
mentioning
confidence: 99%
“…These patterns of TPH degradation were reported by Zucchi et al 2003 andVinas et al 2005 . And similar studies carried out by Cerqueira et al 2011 , demonstrated the degradation of oil sludge by five pure culture isolates viz., Stenotrophomonas acidaminiphila, B. megaterium, B. cereus, B. cibi and Ps.…”
Section: Discussionsupporting
confidence: 78%
“…From the results we can put our hypothesis that the bacteria were the most isolated organism responsible for PCAH decomposition according to their pathway of degradation for complex molecules to get its energy, after changes in pH which would open the pathway for other degradable microbes as fungi, yeast and also algae to reach the Balanced environmental ecosystem in this low nutrient environment.Certain intelligences designated the structure and underlying forces of bacterial community elaborate in bioremediation of crude oil 11,12 ; in this alteration a few group of bacteria were detected to rise the richness in response to oil corruption. During alternative revision off bacterial community on oil polluted soil 13 The heavy metals that were measured in the broth media before and after sludge consuming process refers that some of the heavy metals were reduced but not in high rates for Providencia and Penicilium as qualified strains (Table-4). According to the documented studies, heavy metals in the soil had been reduced by mycorrhized fungus populations 15 .Our results showed that Penicilium as the most qualified fungi in biodegradation process, when compound inoculums of bacterial and fungal content, the bioremediation would be faster and the rate of the heavy metals would be reduced.…”
Section: Resultsmentioning
confidence: 99%